2013
DOI: 10.1080/15332640.2013.830943
|View full text |Cite
|
Sign up to set email alerts
|

Travellers Accessing Addiction Services in Ireland (2007 to 2010): Analysis of Routine Surveillance Data

Abstract: By accessing addiction treatment services recorded in routine national drug treatment data, the characteristics of Irish Travellers were analyzed to understand their needs and develop policies to tackle issues faced by this community. The number of Traveller cases accessing services increased by 163% between 2007 and 2010. Alcohol and opiates were the most common problem substances reported. Traveller women reported high rates of problem opiate use and risky injecting behaviors, contrary to the perception that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It uses the Census categories with the addition of Roma. It includes an option if the service user ‘Does not wish to answer’ or ‘Not recorded’ if there was no opportunity to ask the question, however an analysis of cases from 2007 to 2010 reported that ethnicity was recorded for 99.4% of cases [20]. Secondary data analysis of the NDTRS has been used to provide evidence on addiction services accessed by Irish Travellers [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It uses the Census categories with the addition of Roma. It includes an option if the service user ‘Does not wish to answer’ or ‘Not recorded’ if there was no opportunity to ask the question, however an analysis of cases from 2007 to 2010 reported that ethnicity was recorded for 99.4% of cases [20]. Secondary data analysis of the NDTRS has been used to provide evidence on addiction services accessed by Irish Travellers [20].…”
Section: Resultsmentioning
confidence: 99%
“…It includes an option if the service user ‘Does not wish to answer’ or ‘Not recorded’ if there was no opportunity to ask the question, however an analysis of cases from 2007 to 2010 reported that ethnicity was recorded for 99.4% of cases [20]. Secondary data analysis of the NDTRS has been used to provide evidence on addiction services accessed by Irish Travellers [20]. This evidence has informed the provision of culturally appropriate training for staff and peer workers to support Irish Travellers in accessing addiction services [21].…”
Section: Resultsmentioning
confidence: 99%
“…Opiate use in Ireland as elsewhere is characteristic of socioeconomic disadvantage, low educational attainment and restricted economic opportunity [1, 2]. The most recent capture recapture study of opiate users indicates that opiate use in Ireland is now entering a stabilised phase, with a small decrease in use compared to 2006 and the rate of use among young adults aged 15–24 years declining, and with a visible ageing cohort effect of those in the 35 to 64 years age group [3].…”
Section: Introductionmentioning
confidence: 99%
“…Kelly et al [5] estimated that in 2006 there were between 18,136 and 23,576 opioid users resident in Ireland, with the highest rate of heroin use in Europe at just over 7 cases per 1000 population, and small increases in the older drug using population and in Irish females. National prevalence and treatment data indicated at the time that opiate use was no longer confined to the greater urban context in the capital [1, 5–8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation